Understanding the Drivers of Inhaler Non-Adherence in Asthma and its Influence on Asthma Control - Pathak, Rohit; Pandey, Manoj Kumar; Verma, Shiv Kumar; Kumari, Rinki (Journal of College of Medical Sciences-Nepal, 2024)
Background Asthma remains a significant global health concern, with adherence to inhaler therapy playing a crucial role in its management. Understanding demographic characteristics and adherence behaviours among asthma patients is essential for optimizing treatment outcomes. This study delves into the multifaceted factors associated with non-adherence to inhaler therapy among asthma patients in India, to enhance adherence and improve asthma management outcomes. Methods A cross-sectional study was conducted among 195 asthma patients at Shaikh-UI-Hind Maulana Mahmood Hasan Medical College in Saharanpur, India. Asthma control was assessed using standardized criteria, and adherence to inhaler therapy was evaluated through self-reported questionnaires. Demographic variables including smoking habit, possession of health insurance, comorbidities, duration of asthma, and duration of inhaler use were also recorded. Results Analysis of demographic characteristics revealed a higher prevalence of asthma among females, aged 18-45, and individuals from low-income rural families. Additionally, a substantial proportion of patients had comorbidities and had been diagnosed with asthma for more than five years. Asthma control levels indicated a concerning proportion of patients with poorly controlled asthma, highlighting challenges in achieving optimal management outcomes. Furthermore, significant challenges in adherence to inhaler medication regimens were observed, including medication dosage modification without medical guidance and barriers to proper device use. Conclusions This study reveals significant challenges in asthma control and inhaler adherence, particularly among females and low-income rural patients in India. The patient’s education are essential to address these issues and improve asthma management outcomes.